Tumor-associated macrophages in colon cancer immunotherapy: mechanisms, natural product interventions, and microenvironment remodeling - He, Qingman; Xiang, Li; Luo, Yuanyuan; Wang, Rongrong; Zheng, Chuan; Gao, Yongxiang; Yao, Huan (Frontiers in Immunology, 2025)
Colon cancer persists as a major global health burden due to therapy resistance and metastasis, with tumor-associated macrophages (TAMs) in the microenvironment driving progression through immune evasion and angiogenesis. This review highlights plant-derived therapeutics targeting TAMs to disrupt protumor signaling. Key phytochemicals (e.g., Curcumin, Cucurbitacin B, Astragaloside IV) suppress M2 polarization via NF-κB/STAT3 inhibition, block VEGF/HIF-1α-mediated angiogenesis, and enhance antitumor immunity by downregulating PD-L1. Cannabidiol, Hydroxygenkwanin regulate TAM metabolism. Dietary agents like sulforaphane and β-glucans modulate TAM-gut microbiome crosstalk. Nanoparticle-encapsulated phytochemicals enhance TAM-targeted delivery, while clinical translation requires standardized phytopreparations and biomarker-guided trials. We propose integrating validated botanical adjuvants (e.g., Fucoidan for TLR4 inhibition, dihydroisotanshinone I for CCL2 suppression) with immunotherapies to remodel immunosuppressive niches. Phytotherapy offers a multifaceted strategy to overcome TAM-driven therapeutic barriers in colon cancer, emphasizing plant-based precision medicine to augment conventional treatments.